2020
DOI: 10.2147/opth.s285711
|View full text |Cite
|
Sign up to set email alerts
|

<p>Astigmatic Results of a Diffractive Trifocal Toric IOL Following Intraoperative Aberrometry Guidance</p>

Abstract: Purpose To determine if intraoperative aberrometry (IA) improves astigmatic outcomes for trifocal toric IOL (TTI) cases. Patients and Methods This was a retrospective study examining 137 eyes that underwent cataract extraction and TTI implantation using femtosecond laser, digital registration, and IA. Final cylinder power and axis of placement were determined by IA. Monocular uncorrected distance visual acuity (UDVA), uncorrected intermediate visual acuity (UIVA), uncor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 19 publications
1
24
2
Order By: Relevance
“… 5 Corrective surgery for astigmatism includes corneal incisions, corneal refractive surgery, and toric IOL implantation. 4 Moreover, improved visual outcomes have been reported with the use of toric IOLs than with other corrective surgeries for astigmatism, such as corneal incisions and corneal refractive surgery. 4 Besides refractive accuracy of the postoperative spherical equivalent, reduced postoperative residual astigmatism (≤0.75 D) also plays a crucial role in improving UCVA with trifocal IOLs.…”
Section: Introductionmentioning
confidence: 99%
“… 5 Corrective surgery for astigmatism includes corneal incisions, corneal refractive surgery, and toric IOL implantation. 4 Moreover, improved visual outcomes have been reported with the use of toric IOLs than with other corrective surgeries for astigmatism, such as corneal incisions and corneal refractive surgery. 4 Besides refractive accuracy of the postoperative spherical equivalent, reduced postoperative residual astigmatism (≤0.75 D) also plays a crucial role in improving UCVA with trifocal IOLs.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown similar results in eyes without a history of LVC. 18 , 20 , 21 Therefore, it would appear that the use of IA results in less postoperative astigmatism than preoperative planning alone in post-LVC eyes. With less PRA, both surgeons and patients benefit as there is less need for an enhancement procedure postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 10 We recently published a comparison of the postoperative residual astigmatism (PRA) of the PanOptix trifocal toric (Alcon Vision, LLC, Fort Worth, TX, USA), which followed the ORA recommendation, to back-calculated residual astigmatism (BRA; determined via vector analysis using preoperative cylinder power) that would have resulted using the cylinder power calculated preoperatively. 11 We reported that the proportion of eyes with PRA ≤0.50D was significantly higher using IA (97.8%) versus the preoperative planned cylinder power (87.3%), and that the absolute prediction error (SE) was significantly lower with IA compared to preoperative planning. 11 The purpose of this investigation is to evaluate clinical outcomes of a monofocal toric IOL using digital tracking (DT) and IA and compare it to back-calculated refractive outcomes, which simulate implantation of the preoperative planned power.…”
Section: Introductionmentioning
confidence: 89%
“… 11 We reported that the proportion of eyes with PRA ≤0.50D was significantly higher using IA (97.8%) versus the preoperative planned cylinder power (87.3%), and that the absolute prediction error (SE) was significantly lower with IA compared to preoperative planning. 11 The purpose of this investigation is to evaluate clinical outcomes of a monofocal toric IOL using digital tracking (DT) and IA and compare it to back-calculated refractive outcomes, which simulate implantation of the preoperative planned power.…”
Section: Introductionmentioning
confidence: 89%